Using Radiofrequency Technology to Prevent Retained Sponges and Improve Patient Outcomes. (29th September 2020) - Primiano, Mike; Sparks, Deb; Murphy, Jill; Glaser, Kathleen; McNett, Molly
ABSTRACT: Retained items (eg, sponges, sharps) after surgical procedures are reportable errors that can result in patient harm or death and increased patient and health care system costs. Perioperative use of radiofrequency (RF) technology may decrease the number of retained sponges and reduce hospital costs. We sought to determine whether the use of RF technology may be associated with fewer retained sponges, improved patient outcomes, and decreased hospital costs. We completed a retrospective evaluation of incident reports before and after implementing the use of an RF system for retained surgical sponges. We found that using RF technology was associated with fewer retained sponges and improved outcomes at our facility. We also determined that mortality rates before and after RF technology implementation were similar, and we estimated that our hospital's costs were reduced.